A Combined Ultrasonic Backscatter Parameter for Bone Status Evaluation in Neonates. (1st May 2020) - Mao, Weiying; Du, Yang; Liu, Chengcheng; Li, Boyi; Ta, Dean; Chen, Chao; Zhang, Rong
Abstract : Metabolic bone disease (MBD) is one of the major complications of prematurity. Ultrasonic backscatter technique has the potential to be a portable and noninvasive method for early diagnosis of MBD. This study firstly applied CAS to neonates, which was defined as a linear combination of the apparent integrated backscatter coefficient (AIB) and spectral centroid shift (SCS). The objective was to evaluate the feasibility of ultrasonic backscatter technique for assessing neonatal bone health using AIB, SCS, and CAS. Ultrasonic backscatter measurements at 3.5 MHz, 5.0 MHz, and 7.5 MHz were performed on a total of 505 newborns within 48 hours after birth. The values of backscatter parameters were calculated and compared among gestational age groups. Correlations between backscatter parameters, gestational age, anthropometric indices, and biochemical markers were analyzed. The optimal predicting models for CAS were determined. The results showed term infants had lower SCS and higher AIB and CAS than preterm infants. Gestational age and anthropometric indices were negatively correlated with SCS (| r | = 0.45 – 0.57, P < 0.001), and positively correlated with AIB (| r | = 0.36 – 0.60, P < 0.001) and CAS (| r | = 0.56 – 0.69, P < 0.001). Biochemical markers yielded weak or nonsignificant correlations with backscatter parameters. CAS had relatively stronger correlations with the neonatal variables than AIB and SCS. At 3.5 MHz and 5.0 MHz, only gestational age ( P < 0.001) independently contributed to the measurements of CAS, and could explain up to 40.5% – 44.3% of CAS variation. At 7.5 MHz, the combination of gestational age ( P < 0.001), head circumference ( P = 0.002), and serum calcium ( P = 0.037) explained up to 40.3% of CAS variation. This study suggested ultrasonic backscatter technique was feasible to evaluate neonatal bone status. CAS was a promising parameter to provide more information about bone health than AIB or SCS alone.